Skincare Recommendation System Based on Facial Skin Type with Real-Time Weather Integration - Gabrielle Sheila Sylvagno; Rochadiani, Theresia Herlina (ISB Atma Luhur, 2025)
Skin conditions can be significantly affected by unpredictable weather changes, creating the need for a solution that can provide personalized skincare product recommendations. This study presents the development of an AI-based skincare recommendation system that integrates skin type classification using Convolutional Neural Networks (CNN) with real-time weather data via the OpenWeatherMap API. The system consists of three main components: a ResNet50-based Skin Analyzer, a Weather Analyzer using the Decision Tree algorithm, and a Product Recommendation module. The image dataset is sourced from two Kaggle datasets: